Eksistensi Bahasa Namblong dan Faktor-faktor Penyebab Pergeseran di Kabupaten Jayapura - Mantiri, Grace Janice M.; Iwong, Henry Ch. (Hasta Wiyata, 2023)
The Namblong language is one of the endangered languages. The language is located in Jayapura Regency and has been in contact with speakers of other languages for a long time. Many speakers are not fluent in the language. Many of the older and younger generations have switched to using Papuan Malay in their daily speech. This study aims to describe the existence of the Namblong language and the factors that influence language shift. The approach of this research is sociolinguistic. Data collection methods used observation, interviews and questionnaires. Data analysis method is inductive method. The location of this research is in eleven villages, namely Sermai Atas, Samaikrang, Imsetum, Sermai Bawah, Imeno, Kaitemung, Benyom, Kuimeno, Meyu, Yakotim, and Genyem Besar. The causes of the Namblong language shift are divided into two, namely linguistic and non-linguistic factors. Linguistic factors, namely the namblong language is a spoken language, the duration of the use of Indonesian/Malay is more than the namblong language, the namblong language has become a passive language, and the narrative of namblong is accustomed to the structure of Indonesian/Malay so that it interferes with language, translating code, and mix code. Non-linguistic factors are socio-cultural factors, geography, politics, economy, religion, and education.Â Key words : existence, Namblong, shifting, Jayapura Regency